Heterotipografía : legitimidad y clasificación tipográfica desde una perspectiva de género - Flesler, Griselda (2021)
As part of the cultural changes that have taken place in the social sphere that have been taking place in our country in recent years, the discussion about the intersections of the project field with that of feminist and gender studies has become significant. In an incipient way the field of design has broadened its interest and approach in these subjects. Within this framework, we consider it relevant to offer an articulation of the field of typographic design and gender studies. Our goal is to contribute to the critical analysis of the way in which typographic practices produce generated signifiers. This thesis investigates how Type Foundries, far from being mere distributors, collaborate in the production of heteronormativity as part of the classification processes they carry out. That is, they contribute to defining what is feminine and what is masculine, the characteristics that correspond to them differentially, as well as the formal guidelines of what is right and wrong within the framework of the heteronormativity of the design field. We elaborate the concept of ?Heterotype? to define the ways in which typography reproduces and is crossed by heteronormativity. From this approach, feminist criticisms of the "rule canon" of modern design centered on functionality and neutrality are taken up again and, on the other, approaches from gender studies to explain the mechanisms that define and produce norms of cultural intelligibility through which typefaces are recognized and classified generically. Our gender approach in the field of design does not deal with women and their production, but proposes to think about the conditions of project formulation and how the design works as a significant process. In other words, we consider that this work contributes to the formulation of a generic consciousness in the design practice itself and its significant dimension.